Effects of plyometric training on sonographic characteristics of quadriceps muscle and patellar tendon, quadriceps strength, and jump height in adolescent female volleyball players - Harput, G.; Toprak, U.; Colakoglu, F. F.; Temel, E.; Saylisoy, S.; Baltaci, G. (International Journal of Athletic Therapy & Training, 2022)
The aim of this study was to investigate the effects of plyometric training on vastus lateralis (VL) and patellar tendon size, quadriceps isokinetic strength, and vertical jump height in adolescent female volleyball players. Thirty players (age mean ± SD: 15.7 ± 1.1 years) participated in a 6-week Sportsmetrics™ plyometric training program. VL thickness, echo intensity, and patellar tendon cross-sectional area were assessed by real-time ultrasound. Isokinetic quadriceps strength and vertical jump were assessed. The VL thickness, quadriceps strength, and VJ height increased and VL-echo intensity decreased after training. We recommended that 6-week Sportmetrics plyometric training program may be implemented in adolescent female volleyball programs especially before the beginning of the volleyball season.